U-MATE : Student And Lecturer Location-Based Social Network Aplication - Tombeng, Marchel Thimoty; Mandias, Green F.; Putra, Edson Yahuda (CogITo Smart Journal, 2024)
Students are individuals who pursue higher educcation, have an important role as agents of change and future leaders in various sectors. They are required to actively learn, participate in academic and social activities, and develop critical and innovative thinking. Interactions between students, both with peers and lecturers, play a crucial role in shaping the learning experience on campus. Student interactions with lecturers also have an impact on learning motivation and the lecture experience. The importance of these interactions prompted the researcher to design an application specifically for the campus environment. The app features chat, add friend, and find mate to expand students' social interactions. The find mate feature allows students to find friends randomly, while the maps feature makes it easier for them to find the location of their lecturers and friends in real-time. By integrating the concept of Location-Based Social Network (LBSN), this application is expected to reduce the level of academic stress and improve the quality of interaction among students and with lecturers. Through this application, students can more easily find friends and lecturers, and share locations in real-time. The questionnaire results from Klabat University students showed the need for this kind of application